2021
DOI: 10.2166/nh.2021.061
|View full text |Cite
|
Sign up to set email alerts
|

Decline in net primary productivity caused by severe droughts: evidence from the Pearl River basin in China

Abstract: Understanding the spatiotemporal characteristics of drought events and their impacts on terrestrial net primary productivity (NPP) is crucial for drought mitigation and environmental protection. This study, by taking the Pearl River basin as the case region, investigated drought duration, severity, intensity, affected area, and centroids during 1960–2015 based on the Standardized Evapotranspiration Deficit Index and three-dimensional clustering algorithm and then revealed how these drought characteristics have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Drought events are an important factor causing losses in vegetation NPP. Many studies have investigated the impact of drought on NPP, showing that drought can cause severe losses in NPP [65]. However, real-time monitoring of drought-induced dynamic changes in NPP is difficult, as large-scale NPP data cannot be obtained in real time.…”
Section: Potential For Sif To Monitor Changes In Npp Dynamics Under D...mentioning
confidence: 99%
See 1 more Smart Citation
“…Drought events are an important factor causing losses in vegetation NPP. Many studies have investigated the impact of drought on NPP, showing that drought can cause severe losses in NPP [65]. However, real-time monitoring of drought-induced dynamic changes in NPP is difficult, as large-scale NPP data cannot be obtained in real time.…”
Section: Potential For Sif To Monitor Changes In Npp Dynamics Under D...mentioning
confidence: 99%
“…Our study comprehensively analyzed the relationship between SIF and NPP during two long-term drought events in the HHH Plain at various aspects and scales, discussing and demonstrating the potential of SIF for monitoring dynamic changes in NPP induced Drought events are an important factor causing losses in vegetation NPP. Many studies have investigated the impact of drought on NPP, showing that drought can cause severe losses in NPP [65]. However, real-time monitoring of drought-induced dynamic changes in NPP is difficult, as large-scale NPP data cannot be obtained in real time.…”
Section: Potential For Sif To Monitor Changes In Npp Dynamics Under D...mentioning
confidence: 99%
“…The Pearl River Basin (PRB), which is of great significance for socio-economic development of China, has become the major source of carbon dioxide emissions in China (Zhang et al, 2015). As the PRB is located in a humid area, it has a complex vegetation ecosystem, which is of great significance for local biological carbon sequestration to partially offset fossil fuel emissions (Zhou and Zhou, 2021). However, Deng et al (2018) showed that both drought frequency and severity increased in the PRB, which might weaken the absorption of carbon by vegetation.…”
Section: Introductionmentioning
confidence: 99%